Major concerns in Philippine manufacturing and the role of production and operations management techniques and approaches - Zamora, Elvira A. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1994)
The importance of the production/operations management (P/OM) function is apparent in the face of increasing competition particularly in the global market. There are indications that local manufacturing companies are addressing this concern through the use of appropriate techniques which are intended to improve operations. This paper presents the results of a survey which looked into the major problems of local manufacturing companies and the extent to which they make use of known P/OM approaches.